KEADILAN RESTORATIF PADA KASUS KEKERASAN SEKSUAL BERBASIS ELEKTRONIK DI KEPOLISIAN DAERAH KALIMANTAN BARAT - NIM. A1011201187, ABDURRAHIM (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Electronic-based sexual violence is a form of sexual crime that develops along with the rapid development of Information Technology. Although it has been regulated in Law Number 12 of 2022 on Sexual Violence Crimes and the information and Electronic Transactions Law, the practice of legal handling of electronic-based sexual violence cases in the field still faces the problem of inconsistency in legal norms, especially in relation to the application of restorative justice. This study aims to analyze the practice of restorative justice in the settlement of electronic-based sexual violence cases in the West Kalimantan Regional Police, as well as examine the legal factors and law enforcement officials that affect its implementation. The method used in this study is a juridical-empirical method with a qualitative approach. Primary Data were obtained through interviews with investigators of the West Kalimantan Regional Police Cyber Subdit and criminal law experts, while secondary data were obtained through literature studies on legislation, books, and scientific journals. This study uses the theory of law enforcement by Soerjono Soekanto as a knife analysis. The results showed that the application of restorative justice in the case of electronic-based sexual violence in West Kalimantan Police has not been running optimally. This is due to the inconsistency between the TPKS law which prohibits the settlement of cases outside the criminal justice process, the neutral ITE Law, and the Perpol No. 8 of 2021 that opens a restorative justice space without a firm classification regarding sexually charged cases. In addition, the understanding of law enforcement officers on the scope of electronic-based sexual violence still varies, giving rise to doubts in taking discretion. This study recommends the existence of derivative rules that classify the types of electronic-based sexual violence that can be resolved through restorative justice, in order to provide legal certainty and ensure the protection of victims. (Keywords: electronic-based sexual violence, sexual violence. restorative justice) Abstrak Kekerasan Seksual Berbasis Elektronik (KSBE) merupakan bentuk kejahatan seksual yang berkembang seiring pesatnya teknologi informasi. Meskipun telah diatur dalam Undang - Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS), namun pada praktik penanganan hukum terhadap kasus KSBE di lapangan masih menghadapi persoalan ketidaksinkronan norma hukum, khususnya dalam kaitannya dengan penerapan keadilan restoratif. Penelitian ini bertujuan untuk menganalisis praktik keadilan restoratif dalam penyelesaian perkara KSBE di Polda Kalimantan Barat, serta menelaah faktor-faktor hukum dan aparat penegak hukum yang memengaruhi implementasinya. Metode yang digunakan dalam penelitian ini adalah metode yuridis - empiris dengan pendekatan kualitatif. Data primer diperoleh melalui wawancara dengan penyidik Subdit Siber Polda Kalimantan Barat, Akademisi, dan Praktisi Hukum. Sedangkan, data sekunder diperoleh melalui studi kepustakaan terhadap peraturan perundang-undangan, buku, dan jurnal ilmiah. Penelitian ini menggunakan teori penegakan hukum oleh Soerjono Soekanto sebagai pisau analisis. Hasil penelitian menunjukkan bahwa penanganan KSBE di Kalimantan Barat belum optimal, karena masih ada penerapan keadilan restoratif dalam kasus KSBE di Polda Kalimantan Barat. Hal ini disebabkan oleh ketidaksinkronan antara UU TPKS yang melarang penyelesaian perkara di luar proses peradilan pidana, UU ITE yang bersifat netral, serta Perpol No. 8 Tahun 2021 yang membuka ruang keadilan restoratif tanpa klasifikasi tegas mengenai kasus-kasus bermuatan seksual. Selain itu, pemahaman aparat penegak hukum terhadap ruang lingkup KSBE masih bervariasi, sehingga menimbulkan keraguan dalam mengambil diskresi. Penelitian ini merekomendasikan adanya aturan turunan yang mengklasifikasikan jenis-jenis KSBE yang dapat diselesaikan melalui keadilan restoratif, guna memberikan kepastian hukum dan menjamin perlindungan korban. (Kata kunci: kekerasan seksual berbasis elektronik, kekerasan seksual, keadilan restoratif)